2005
DOI: 10.1039/b415471a
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of dipyrido-[3,2-a:2′,3′-c]-phenazine (dppz) by photolysis in ethanol solution

Abstract: Photolysis of dipyrido-[3,2-a:2',3'-c]-phenazine (dppz) (1) in ethanol solution leads to the formation of 9,14-dihydrodipyridophenazine (2), which has been characterised by detailed NMR analysis, UV/VIS absorption spectroscopy, and theoretical calculations which reveal that its red colour is due to a low-lying intramolecular charge transfer state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 9 publications
3
29
0
Order By: Relevance
“…Illumination of 3 in acetonitrile under aerobic conditions does not lead to any observable oxidation of the central tatpp ligand structure. Even prolonged irradiation over 72 h did not result in the formation of detectable amounts of the corresponding oxidation product [(tbbpy) 2 Ru(tatpq)Ru(tbbpy) 2 ](PF 6 ) 4 . It should be noted that peroxy disulfate oxidation of 3 and related bpy and phen analogues quantitatively yields the quinone (tatpq) products.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Illumination of 3 in acetonitrile under aerobic conditions does not lead to any observable oxidation of the central tatpp ligand structure. Even prolonged irradiation over 72 h did not result in the formation of detectable amounts of the corresponding oxidation product [(tbbpy) 2 Ru(tatpq)Ru(tbbpy) 2 ](PF 6 ) 4 . It should be noted that peroxy disulfate oxidation of 3 and related bpy and phen analogues quantitatively yields the quinone (tatpq) products.…”
Section: Resultsmentioning
confidence: 99%
“…[10,11] To the best of our knowledge, this is the first time that such a product has been isolated in good yield and the structure was confirmed by X-ray crystallography. [3,4]phenazine-11,16-quinone, dpbqz. [8] We postulate that the oxidation process involves singlet oxygen which is created by triplet sensitisation from the excited ruthenium 3 MLCT state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Theinvestigations towards the effect of blue-light irradiation of the catalytic reaction mixture containing BNA + clearly showed that once the doubly reduced Ru-(tpphz)RhCp* state is formed, photoexcitation impedes the catalytic hydrogenation of BNA + to BNAH. To the best of our knowledge,wepresented, for the first time,the results of in-situ early-time photodynamics of an isolated, molecular photocatalyst in its active electronic configuration.…”
Section: Resultsmentioning
confidence: 99%
“…[11] In addition, a recent report by Kelly et al highlights its specific photochemical behavior. [12] The herein reported novel organic compound TTF-dppz (1), which emerges from the annulation of sulfur-and nitrogen-containing polycycles, allows a thorough experimental and theoretical study of photoinduced charge transfer (CT) in a single D-A molecule. In fact, this transfer occurs between spatially separated electron-rich and electron-deficient fragments within the extended polycyclic system.…”
Section: Introductionmentioning
confidence: 99%